INTERFACE DESIGN TEMPERATURE CONTROL SYSTEM USING computer-based C PROGRAMMING LANGUAGE - Okti Nur Yudhanti Kusumaningtyas (JAKSTIK Journal, 2004)
Along with the development of science and technology, has had a positive impact in the industrial world, especially in the utilization of the temperature measurement system that uses the principle of data acquisition. With the computer, then use the computer to control a temperature measurement system is now a practical and common. In industries that require extremely high temperatures on the production process, the temperature should be maintained at certain temperatures. Therefore, this paper aims to facilitate the temperature control in an industry that requires high temperatures in its operations. As of this writing, the series of temperature control systems can work well, although there are deviations from the value of the actual value. This is supported by the performance of individual components within the system. If each component in the system can work in accordance with their respective functions, the system will have the reliability (reliability) in order to work properly. For ease in the observation, the authors use a table test. Table test was used to determine the level of deviation from the data obtained with actual data. Table testing can also be used as a way to process the data using least squares method, so it is easy in analyzing.